2020
DOI: 10.3390/ijms22010331
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of KLF10 Leads to Stress-Induced Liver Fibrosis upon High Sucrose Feeding

Abstract: Liver fibrosis is a consequence of chronic liver injury associated with chronic viral infection, alcohol abuse, and nonalcoholic fatty liver. The evidence from clinical and animal studies indicates that transforming growth factor-β (TGF-β) signaling is associated with the development of liver fibrosis. Krüppel-like factor 10 (KLF10) is a transcription factor that plays a significant role in TGF-β-mediated cell growth, apoptosis, and differentiation. In recent studies, it has been reported to be associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 58 publications
1
26
0
Order By: Relevance
“…The link between altered metabolic homeostasis and inflammation is well established (Saltiel and Olefsky, 2017). Recent studies have highlighted the role of KLF10 in regulating inflammation (Huang et al, 2016;Wara et al, 2020;Yang et al, 2020) and in attenuating liver injury in mice with NASH ad fibrosis (Lee et al, 2020). In this study, we found apoptosis and inflammation related processes as gene sets that gain circadian coordination in unchallenged hepKO mice.…”
Section: Discussionsupporting
confidence: 56%
“…The link between altered metabolic homeostasis and inflammation is well established (Saltiel and Olefsky, 2017). Recent studies have highlighted the role of KLF10 in regulating inflammation (Huang et al, 2016;Wara et al, 2020;Yang et al, 2020) and in attenuating liver injury in mice with NASH ad fibrosis (Lee et al, 2020). In this study, we found apoptosis and inflammation related processes as gene sets that gain circadian coordination in unchallenged hepKO mice.…”
Section: Discussionsupporting
confidence: 56%
“…Besides, KLF10 expression could be induced by carbohydrate response element‐binding protein (ChREBP) upon glucose stimulation in mouse hepatocytes (Iizuka et al , 2011). KLF10 knockout mice exhibited significant hepatic steatosis, inflammation, and liver injury upon high sucrose diet feeding (Lee et al , 2020). T cell‐specific KLF10 knockout mice were susceptible to diet‐induced obesity, insulin resistance, and fatty liver (Wara et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Krüppel-like factors ( KLFs ) are transcription factors that play pivotal roles in diseases. For example, KLF10 -deficient mice on a high-sucrose diet promoted the progression of hepatic steatosis, inflammation, and fibrosis compared to wild-type mice [ 24 ]. Another study showed that KLF15 can activate twist-related protein 2 ( TWIST2 ) to ameliorate liver steatosis and inflammation by modulating nuclear factor ( NF ) -κB or sterol regulatory element-binding protein 1c ( SREBP1c )-fibroblast growth factor 21 ( FGF21 ) signaling pathways [ 25 ].…”
Section: Important Molecules and Their Mediated Signaling Pathways In Nafld And Nashmentioning
confidence: 99%
“…In addition, there are some other targets for NAFLD and NASH treatments, such as G protein-coupled receptors ( GPCRs ) [ 142 ], estrogen-related receptor alpha ( ERRα ) [ 143 ], bone morphogenetic proteins ( BMPs ) [ 144 ], and KLFs [ 24 , 145 ]. The treatment options for NAFLD/NASH are summarized in the graphic picture ( Figure 2 ).…”
Section: Treatment Options For Nafld and Nashmentioning
confidence: 99%